Early results of primary total hip arthroplasty performed in young adults at a regional Saudi-Arabian orthopedics center: a prospective observational study - Walid M. Al-Shaer; Ali H. Al-Yami; Mokhtar Ahmed Al-Sayed; Ali Mohammed Al-Zaidan; Emad Ruddah Al-Sufyani; Ahmed A. Khalifa; Raad M. M. Al-Thaqafi; Abdulmohsen H. Al-Hamyani; Mohammed M. Al-Subaie (Travmatologiâ i Ortopediâ Rossii)
Background. Younger patients undergoing primary total hip arthroplasty (THA) have different indications and outcomes than elderly patients. Furthermore, studies reporting the results of THA in young patients are scarce in our area.